2021
DOI: 10.3390/agriculture11070574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forage Processor Roll Gap Width and Storage Length on Fermentation Profile, Nutrient Composition, Kernel Processing Score, and Starch Disappearance of Whole-Plant Maize Silage Harvested at Three Different Maturities

Abstract: Our objective was to assess the effect of forage processor roll gap width and storage length on fermentation, nutrient composition, kernel processing score (KPS), and ruminal in situ starch disappearance (isSD) of whole-plant maize silage harvested at different maturities. Samples from a single maize silage hybrid at three harvest maturities (1/4, 1/2, and 3/4 kernel milk line (early, intermediate, and late, respectively)) processed with two roll gap widths (1 and 3 mm) were collected and stored in quadruplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…To improve the availability of starch in maize silage, it is essential to improve the processing of maize grain (Beauchemin & Yang, 2005). Maize silage is an important source of not only the required energy source in the form of starch but also coarse structural fibre (Saylor et al, 2021). Our values are consistent with the literature, as the general principle is that the higher the dry matter content, the shorter the length of the cut must be.…”
Section: Resultssupporting
confidence: 87%
“…To improve the availability of starch in maize silage, it is essential to improve the processing of maize grain (Beauchemin & Yang, 2005). Maize silage is an important source of not only the required energy source in the form of starch but also coarse structural fibre (Saylor et al, 2021). Our values are consistent with the literature, as the general principle is that the higher the dry matter content, the shorter the length of the cut must be.…”
Section: Resultssupporting
confidence: 87%
“…This the average daily dry gain and the average climatic conditions (RKPP) with R 2 0.069. The average daily dry gain in experiments with one silage hybrid in subtropical conditions in the vegetation stages starting with the ½ milk line stage at the grain value of 4.18 ±1.07 g/kg/ day (Saylor et al, 2021) and 4.88 ±1.74 g/kg/day (Rabelo et al, 2015), which is consistent with our results with The average dry matter content of 30% (silage maturity) in the whole set of measurements (n 1,320) was reached on the 153 rd vegetation day and the 273 rd calendar day. In terms of individual experiments, the fastest development in achieving silage maturity was in the NL 2018 season (Figure 1; Table 4).…”
Section: Dry Matter Content By Season and Experiments And In Relation...mentioning
confidence: 99%
“…Dias et al [23] compared the effect of different types of maize processing on starch disappearance and observed that a higher starch disappearance in the rumen was associated with a higher percentage of starch passing through a 4.75 mm sieve. In addition, Saylor et al [11] postulated that more aggressive processing of kernels between rolls leads to increased starch digestibility. This corresponds to our results, where both SHR and MAX had higher kernel processing, leading to higher starch disappearance after 24 h incubation.…”
Section: In Situ Rumen Disappearancementioning
confidence: 99%
“…Another new technology is the MCC MAX rollers, where there is a possibility of a range of cut lengths of 10 to 22 mm. By reducing the gap between the rollers to 1 mm, this technology is able to significantly increase the kernel breakage in maize silage, even during late maize harvesting [11]. The studies published to date have mainly been devoted to the assessment of conventional and Shredlage technologies.…”
Section: Introductionmentioning
confidence: 99%